A Contour Approach to Thinning Algorithms - Peter Tarabek (Communications - Scientific letters of the University of Zilina, 2009)
Thinning algorithms are widely used in many image processing tasks. Many thinning algorithms were proposed but they usually tend to process all image pixels in every iteration. Two approaches to contour thinning are described and a short discussion about their features is given. These approaches can be implemented as sequential or parallel algorithms with different deletion rules. Results of comparison and analysis are presented in this paper.